2010
DOI: 10.5851/kosfa.2010.30.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characteristics and Immunomodulating Activity by Lactobacillus paracasei subsp. paracasei BFI46 Isolated from New-Born Infant Feces

Abstract: In order to develop a new starter for fermented milk, Lactobacillus paracasei subsp. paracasei BFI46 (BFI46) obtained from new-born infant feces was investigated for physiological characteristics. Good immunomodulating activity was evident compared with commercial lactic acid bacteria starter cultures. The optimum growth temperature of BFI46 was 40 o C with 12 h required to reach pH 4.3. Testing with 13 different antibiotics revealed greatest sensitivity of BFI46 to penicillin-G and chloramphenicol, and height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
4
3
0
Order By: Relevance
“…The log value of population after 7 h incubation without 0.3% oxgall was 9 but 8.4 with the addition of 0.3% bile so that it has shown good bile tolerance. This result is similar to the report of Lim et al (2010) on the bile tolerance of L. paracasei subsp. paracasei BFI46 that it has shown slight decrease in the log value of population from 9 to 8.5.…”
Section: Antibiotic Tolerancesupporting
confidence: 82%
See 2 more Smart Citations
“…The log value of population after 7 h incubation without 0.3% oxgall was 9 but 8.4 with the addition of 0.3% bile so that it has shown good bile tolerance. This result is similar to the report of Lim et al (2010) on the bile tolerance of L. paracasei subsp. paracasei BFI46 that it has shown slight decrease in the log value of population from 9 to 8.5.…”
Section: Antibiotic Tolerancesupporting
confidence: 82%
“…The leucine arylamidase and acid phosphatase activity was 5 and it was relatively high on the other hand β-glucuronidase activity of carcinogen-producing enzymes in the gut was negative and there was no enzyme activity. This result is similar to the report of Lim et al (2010) on the β-glucuronidase activity of L. paracasei subsp. paracasei BFI46.…”
Section: Antibiotic Tolerancesupporting
confidence: 82%
See 1 more Smart Citation
“…The leucine arylamidase and acid phosphatase activity was 5 and it was relatively high on the other hand β-glucuronidase activity one of carcinogen-producing enzymes in the gut was 0 and it was no enzyme activity. This result is similar trends to the report of Lim et al (2010) on the β-glucuronidase activity of L. paracasei subsp. paracasei BFI46.…”
Section: Antibiotic Tolerancesupporting
confidence: 81%
“…L. fermentum LC272 showed more sensitive to rifampicin and penicillin-G in a comparison of 14 different antibiotics, and showed most resistance to streptomycin and gentamycin. Lim et al (2010) has reported that L. paracasei subsp. paracasei BFI46 was sensitive to penicillin-G and chloramphenicol but it shown high resistance to neomycin, kanamycin and polymycin.…”
Section: Antibiotic Tolerancementioning
confidence: 99%